Effect of Rumensin on the growth and sexual development of beef bulls - Corah, L.R.; Busby, W.D.; McKee, R.M.; Kiracofe, G.H. (Kansas State University. Agricultural Experiment Station, 2011)
Fifty percentage Simmental bull calves were fed either with or without Rumensin. Although Rumensin improved gain by 9.2%, it had no effect on sexual development.
Keywords: Beef; Growth; Sexual development; Bulls